2007
DOI: 10.1016/j.aca.2007.05.032
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of 17 ginsenosides in rat urine by ultra performance liquid chromatography–mass spectrometry with solid-phase extraction

Abstract: A rapid analytical method for quantifying 17 ginsenosides in rat urine by ultra performance liquid chromatography (UPLC) coupled to electrospray ionization mass spectrometry (ESI-MS) is described. All analytes were extracted by solid-phase extraction optimized to obtain good recovery and quantified using digoxin as an internal standard. ESI-MS was optimized for different cone voltages at positive ionization mode to allow simultaneous analysis of all analytes in a relatively short time. Qualitative methodologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 15 publications
0
29
0
1
Order By: Relevance
“…Studies which used positive ion mode electrospray for the analysis of ginsenosides indicated that the predominant and almost exclusive ion observed was the [M + Na] + ion (Cui et al 2001, Wang et al, 2007. van Breeman et al (1995) reported that the addition of Na + as NaCl did not improve the sensitivity.…”
Section: Lc-ms Of Ginsenosidesmentioning
confidence: 97%
See 3 more Smart Citations
“…Studies which used positive ion mode electrospray for the analysis of ginsenosides indicated that the predominant and almost exclusive ion observed was the [M + Na] + ion (Cui et al 2001, Wang et al, 2007. van Breeman et al (1995) reported that the addition of Na + as NaCl did not improve the sensitivity.…”
Section: Lc-ms Of Ginsenosidesmentioning
confidence: 97%
“…Another sample preparation procedure for the analysis of ginsenoside and metabolites has been illustrated by a number of authors (Sun et al, 2005;Wang et al, 2007;Yu et al, 2007a, b) and involves solid-phase extraction with vacuum manifolds:…”
Section: Sample Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…Além dos trabalhos descritos acima, outros foram realizados empregando CLUE, como, por exemplo, determinação de lactonas, 23 to- xinas marinhas, 45 cianobactérias, 46 drogas veterinárias, 47 saponinas, 12,48 enzimas 49 e metabonomas, 50 o que comprova que a cromatografia líquida de ultra eficiência vem sendo avaliada e empregada em diversas áreas.…”
Section: Aplicações Da Clueunclassified